2006
DOI: 10.1002/ejic.200600375
|View full text |Cite
|
Sign up to set email alerts
|

Bis‐Ruthena(III)cycles [Ru(CN)2(NN)]PF6 as Low‐Potential Mediators for PQQ Alcohol Dehydrogenase (CN = 2‐phenylpyridinato or 4‐(2‐tolyl)pyridinato, NN = bpy or phen)

Abstract: Bis‐cyclometalated analogs of tris(2,2′‐bipyridine)ruthenium(II), namely [RuIII(C∩N)2(N∩N)]PF6 complexes 3, are prepared in 52–57 % yield from the mono‐cyclometalated N,N‐dimethylbenzylamine (dmbaH) derivatives [RuII(dmba)(N∩N)(MeCN)2]PF6 (N∩N = bpy or phen) and mercurated 2‐phenylpyridinato‐ or 4‐(2‐tolyl)pyridinato (C∩N) species Hg(C∩N)Cl. Two new bis‐ruthenacycles studied by X‐ray crystallography revealed a C1 symmetry, with the C and N atoms of different C∩N ligands trans to the nitrogen atoms of the N∩N l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…The E 1/2 values for Ru II/I couples are usually very negative for those Ru II complexes with N-donor ligands, but N-donor ligands are usually used to generate Ruoxo complexes in high oxidation states. [33] Also, the oneelectron reduction potentials of most Ru IV =O complexes reported in the literature are not high. [34] Together these contribute to why WNA has not been proposed for Ru IV =O systems.…”
Section: Ru V =O Versus Ru Iv =O In Water Oxidationmentioning
confidence: 96%
“…The E 1/2 values for Ru II/I couples are usually very negative for those Ru II complexes with N-donor ligands, but N-donor ligands are usually used to generate Ruoxo complexes in high oxidation states. [33] Also, the oneelectron reduction potentials of most Ru IV =O complexes reported in the literature are not high. [34] Together these contribute to why WNA has not been proposed for Ru IV =O systems.…”
Section: Ru V =O Versus Ru Iv =O In Water Oxidationmentioning
confidence: 96%
“…Thus, Yam et al reported higher values (1.66–1.86 V) for complexes 122a – d that bear an aminocarbene C,C ligand; on the basis of theoretical calculations, they considered that the HOMO involved in the irreversible oxidation process was not purely metal‐centred 186. Conversely, values in the –0.66 to –0.35 V range were found for ruthenium complexes 50a – d ,102 111 166,171,195,196 and 136b ,197 which are characterized by a high electron density at the metal, either because of anionic ancillary ligands or because of double cyclometallation.…”
Section: Physicochemical Propertiesmentioning
confidence: 98%
“…Homoleptic bis‐chelated Ru III complexes 50 were similarly prepared by Ryabov et al102 starting from bis(solvato) cyclometallated complexes of Ru II and a chloridomercurated derivative of 2‐phenylpyridine (Scheme ): oxidation of the metal centre to the +3 oxidation states was caused by the inherent low Ru II /Ru III oxidation potential (from –0.21 to –0.25 V vs. SCE) of tris‐chelated Ru II species. It must be outlined that this method is the second known to date for the preparation of homoleptic OC ‐6 bisruthenacycles.…”
Section: Cycloruthenationmentioning
confidence: 99%
“…In principle, an electrophilic metal center MX n can react with a chelate L-ArH to produce (L-Ar)MX nÀ1 and HX, where X is likely to be halide, OTf, O 2 CCF 3 , etc. Transition metal triflates are an attractive class of starting materials for an exploratory study of this type, and 2-phenyl-pyridine has considerable precedent in heterolytic CH-bond activations [8][9][10][11][12][13][14][15][16][17][18]. The use of Ni(OTf) 2 [19] as a starting material capable of heterolytically activating 2-phenyl-pyridine, and subsequent reactivity studies are reported herein.…”
Section: Introductionmentioning
confidence: 98%